Forage Potential Of Ruminated Animal Feed In Oil Palm Plantation Owned By Pt. Nusa Ina Group In The District Of North East Seram Kobi Central Maluku Regency - Renmaur, Ledrina Robeka; Patty, Christian Willem; Eoh, Marna (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2022)
This study aims to determine the botanical composition, production of forage animal feed and capacity in oil palm plantation owned by PT. Nusa Ina Group which is in the District of North East Seram Kobi. This study uses a survey method through direct observation and measurement of forage in the oil palm plantation area at PT. Nusa Ina Group in the District of North East Seram Kobi. The results showed that the The botanical composition of the pasture in the oil palm plantation area of ​​PT.Nusa Ina group in the sub-district of North Seram, Kobi based on dry weight is dominated by 33.73% carpet grass. The older the age of the oil palm plant, the less the number of species found in the plantation area and the less potential for fresh forage production and forage dry matter production, ranging from 5,794.41 kg/ha fresh weight and dry weight 1,121.80 kg/ha. The grazing capacity for ruminant livestock in the oil palm plantation area of ​​PT. Nusa Ina Group is quite good, namely 0.67 Ha / UT and is estimated to accommodate 442.2 UT / yr with an area of ​​660 Ha.